Discursos da BNC-Formação enquanto mecanismos da biopolítica, noopolítica e psicopolítica : possíveis assujeitamentos de professores na educação - Nascimento Junior, Vamberto Marinho do (My University, 2022)
The objective of this dissertation is to analyze how the discourses of BNC-Formação, as mechanisms of Biopolitics, Noopolitics and Psychopolitics, produce possible subjugation of teachers in education. The methodology is based on Michel Foucault's archeogenealogy, with theoretical contributions from Nietzsche, Lazzarato, Han, Laval and Mészáros. The research problem is "how do the discourses of BNC-Formação, as mechanisms of Biopolitics, Noopolitics and Psychopolitics produce possible subjection of teachers in basic education?". The documentary analysis was based on two researches on the professional situation of teachers, at BNCC and BNC-Formação. The second chapter presents the archaeogenealogy method, the state of knowledge and data on the teachers' work situation. Next, an analysis is made of the concepts of Biopolitics, Noopolitics and Psychopolitics, the development of neoliberalism from Foucault's perspective and the relation between neoliberalism and education in Brazil. Finally, we made excerpts from the BNC-Formação document to understand its teacher training objectives; next, we presented the manifestations of educational institutions contrary to the document; then, we investigated the concept of 'competences' from BNC-Formação; and, finally, the examination and analysis of how the discourses of BNC-Formação as a Biopolitical, Noopolitical and Psychopolitical mechanism produce the possible subjugation of teachers. The development of market competencies in Brazilian education, through BNC-Formação, converts the professional dynamics of teachers in Basic Education, with the creation of possible mechanisms of subjugation to economic demands. The analysis of this scenario is the basis of this research, as a way of coping with situations of manipulation, oppression and silencing of teachers. [resumo fornecido pelo autor]
O objetivo desta dissertação é analisar como os discursos da BNC-Formação, enquanto mecanismos da Biopolítica, Noopolítica e Psicopolítica, produzem possíveis assujeitamentos de professores na educação. A metodologia baseia-se na arqueogenealogia de Michel Foucault, com contribuições teóricas de Nietzsche, Lazzarato, Han, Laval e Mészáros. O problema de pesquisa é "como os discursos da BNC-Formação, enquanto mecanismos da Biopolítica, Noopolítica e Psicopolítica produzem possíveis assujeitamentos de professores na educação básica?". A análise documental baseou-se em duas pesquisas sobre a situação profissional dos professores, na BNCC e BNC-Formação. O segundo capítulo apresenta o método da arqueogenealogia, o estado do conhecimento e dados sobre a situação de trabalho dos professores. A seguir, faz-se a análise dos conceitos de Biopolítica, Noopolítica e Psicopolítica, a formação do neoliberalismo na perspectiva de Foucault e a relação entre neoliberalismo e educação no Brasil. Por fim, realizamos recortes do documento da BNC-Formação para compreender seus objetivos de formação docente; na sequência, apresentamos as manifestações das instituições educacionais contrárias ao documento; após, investigamos o conceito de 'competências' da BNC-Formação; e, por fim, a investigação e a análise de como os discursos da BNC-Formação enquanto mecanismo Biopolítico, Noopolítico e Psicopolítico produzem o possível assujeitamento dos professores. O desenvolvimento de competências de mercado na educação brasileira, por meio da BNC-Formação, transforma a dinâmica profissional dos professores na Educação Básica, com a criação de possíveis mecanismos de assujeitamento às demandas econômicas. A análise desse cenário é a base desta pesquisa, como forma de enfrentamento às situações de manipulação, opressão e silenciamento dos professores. [resumo fornecido pelo autor]
Keywords: Base Nacional Comum Curricular - Formação; Professores - Brasil; Educação básica; Educação e Estado; Common National Curriculum Base - Training of; Teachers - Brazil; Basic education; Education and state